Prevalence of Culture-Confirmed Tuberculosis Among Patients with Nontuberculous Mycobacterial Disease - He Y; Wang JL; Zhang YA; Wang MS (Infection and Drug Resistance, 2022)
Yu He,1 Jun-Li Wang,2 Yan-An Zhang,3,4 Mao-Shui Wang4– 6 1Department of Clinical Laboratory, First Affiliated Hospital of Guangxi Medical University, Nanning, 530021, People’s Republic of China; 2Department of Laboratory Medicine, The Affiliated Hospital of Youjiang Medical University for Nationalities, Baise, People’s Republic of China; 3Department of Cardiovascular Surgery, Shandong Public Health Clinical Center, Cheeloo College of Medicine, Shandong University, Jinan, 250013, People’s Republic of China; 4Shandong Key Laboratory of Infectious Respiratory Disease, Jinan, Shandong, People’s Republic of China; 5Department of Laboratory Medicine, Shandong Provincial Chest Hospital, Cheeloo College of Medicine, Shandong University, Jinan, 250013, People’s Republic of China; 6Department of Lab Medicine, Shandong Public Health Clinical Center, Cheeloo College of Medicine, Shandong University, Jinan, 250013, People’s Republic of ChinaCorrespondence: Yan-An Zhang, Department of Cardiovascular Surgery, Shandong Public Health Clinical Center, 46# Lishan Road, Jinan, 250013, People’s Republic of China, Email zhangtbgroup@163.com Mao-Shui Wang, Department of Laboratory Medicine, Shandong Public Health Clinical Center, 46# Lishan Road, Jinan, 250013, People’s Republic of China, Email wangmaoshui@gmail.comBackground: Currently, the prevalence of nontuberculous mycobacteria (NTM) strains isolated from mycobacterial cultures has been well characterized. However, the data on the prevalence of tuberculosis (TB) in patients with NTM disease remain unclear.Methods: Between January 2012 and August 2020, consecutive patients with positive mycobacterial cultures were included for analysis. The identification of Mycobacteria spp. was performed using the DNA array method or sequencing of 16S rDNA. NTM disease is diagnosed when the same infectious agent is identified in at least two sputum or is identified in sterile samples.Results: A total of 997 strains were isolated from 828 inpatients. Of them, 261 inpatients (31.5%) were diagnosed as NTM disease. The mean age of the 261 patients was 55.7 ± 15.5 years old and 64.0% (n = 167) of them were male. The prevalence of culture-confirmed TB patients among patients with NTM disease was estimated as 8.0% (21/261).Conclusion: TB is common in NTM disease and caution should be taken when initiating the treatment of NTM disease.Keywords: prevalence, tuberculosis, culture, nontuberculous mycobacteria, diagnosis